Abundance of pests and diseases in Arabica coffee production systems in Uganda - ecological mechanisms and spatial analysis in the face of climate change. - Liebig, Theresa Ines (2017)
Coﬀee production worldwide is threatened by a range of coﬀee pests and diseases (CPaD). Integrated management options require an understanding of the bioecology of CPaD and the prevalent interdependencies within the agroecological context. The comparison of diﬀerent shading systems (e.g. shade-grown vs. sun-grown coﬀee) and the identiﬁcation of tradeoﬀs for ecosystem services is still a matter of ongoing debates. There is little quantitative knowledge of ﬁeld-level investigation on shade eﬀects and its ecological mechanisms across environmental and shading system gradients. Considering the increasingly evident eﬀects of progressive climate change on CPaD, the need to examine the balance of shade eﬀects under diﬀerent environmental conditions becomes apparent. With the example of the coﬀee growing region of Mt Elgon, Uganda, this project aimed at addressing the complexity of shading eﬀects on economically relevant CPaD using environmental and production system gradients. The approach was designed in an interdisciplinary manner, to involve the broader context of coﬀee agroforestry systems. The ﬁrst two chapters of this thesis dealt with general aspects of coﬀee smallholder farming. The diversity of existing coﬀee production systems was characterized along an altitudinal gradient. A typology of production systems based on indicators related to the vegetation structure was generated and classiﬁed as coﬀee open canopy, coﬀeebanana inter-cropping, and densely shaded coﬀee systems. The typology served as the basis for comparison across the environmental and production system gradients. In the second chapter, farmers’ knowledge on CPaD and the role of shade trees was contrasted with expert knowledge and ﬁeld observations. Discrepancies regarding CPaD symptomatology, management and response to shade were revealed. Tackling institutional obstacles and disentangling shading eﬀects are therefore a priority for the improvement of plant health management. The last two chapters focused more speciﬁcally on biophysical aspects of Coﬀee Leaf Rust (CLR, Hemileia vastatrix) and White Coﬀee Stem Borer (WCSB, Monochamus leuconotus). The eﬀects of environment and production system on CLR abundance were spatio-temporally variable and either directly, interactive or indirectly mediated by microclimate. The development of white coﬀee stem borer was controlled by the bimodal rainfall, and by altitude and shade through their eﬀect on minimum temperature. The ﬁndings emphasize the enormous importance of micro-environments for the ecology of CPaD, not least because of its implications in the context of climate change.